THE EFFECT OF ONLINE ADVERTISING ON CONSUMER BUYING INTEREST IN ONLINE SELLING APPLICATIONS WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE (Case Study of Medical Doctor and Nurses in Chicago) - Mark G. Maffett; Jorge O. Brusa (PT. Radja Intercontinental Publishing, 2022)
The results of this study show. (1) It can be seen that the value of the adjusted R square is 0.758 or 75.8%. This shows that consumer satisfaction (Y1) and advertising (X) can explain purchase intention (Y2) of 75.8%, the remaining 24.2% (100% - 75.8%) is explained by other variables outside the research model. This. Such as service, price and interest in buying. (2) The results of the (Partial) t test show that tcount (7.413) > ttable (1.685), likewise with a significance value of 0.00 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the advertising variable (X) has an effect positive and significant to consumer satisfaction (Y1). (3) The results of the t test (Partial) can be seen that the value of tcount (3.059) > ttable (1.685), and the significance value is 0.00 <0.05, it can be concluded that the second hypothesis is accepted, meaning that advertising (X) has a positive and significant effect on purchase intention (Y2). (4) The results of the path analysis test show that the direct effect of variable X on variable Y2 is 0.377. While the indirect effect through the Y1 variable is 0.769 x 0.554 = 0.426, the calculation results obtained show that the indirect effect through the Y1 variable is greater than the direct effect on the Y2 variable.